2016
DOI: 10.1016/j.cgh.2015.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mirtazapine in Patients With Functional Dyspepsia and Weight Loss

Abstract: In a randomized, placebo-controlled trial, mirtazapine significantly improved early satiation, quality of life, gastrointestinal-specific anxiety, nutrient tolerance, and weight loss in patients with FD. ClinicalTrials.gov number: NCT01240096.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 38 publications
2
89
0
6
Order By: Relevance
“…However, through their effects on gastrointestinal motility, they could also exert therapeutic effects in PDS, as described for 5-HT1A agonists that act on gastric accommodation. The antidepressant mirtazapine, when taken at a low dose in the evening, has also shown efficacy for the treatment of early satiety and nausea in patients with functional dyspepsia with weight loss who had no clinically relevant depression or anxiety comorbidity 197 .…”
Section: Pharmacological Treatment Of Pdsmentioning
confidence: 99%
“…However, through their effects on gastrointestinal motility, they could also exert therapeutic effects in PDS, as described for 5-HT1A agonists that act on gastric accommodation. The antidepressant mirtazapine, when taken at a low dose in the evening, has also shown efficacy for the treatment of early satiety and nausea in patients with functional dyspepsia with weight loss who had no clinically relevant depression or anxiety comorbidity 197 .…”
Section: Pharmacological Treatment Of Pdsmentioning
confidence: 99%
“…Current treatment options for FD are limited, as developing treatments has been challenging due to the heterogeneous nature of the condition, especially for complicated disorders between central and peripheral functions. Therefore, the efficacies of acid suppressants, prokinetics, and anxiolytics have remained low, because these drugs address only part of this diverse pathophysiology . Together with these findings, characteristic drugs acting for both directions (the gut‐brain axis) may be required to treat FD.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in relation to gastroparesis, symptom control is mirtazapine’s agonism of central and peripheral 5-HT1A serotonin receptors. This receptor is known to contribute to gastric receptive fundic relaxation, and its stimulation by mirtazapine has been shown in multiple double-blinded, randomized, placebo-controlled trials to improve symptom control, weight loss, early satiation, and overall quality of life in patients with functional dyspepsia 47. It has been recognized as an effective antiemetic in several settings: palliative care, chemotherapy patients, postsurgery patients, and even idiopathic nausea and vomiting 813.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized as an effective antiemetic in several settings: palliative care, chemotherapy patients, postsurgery patients, and even idiopathic nausea and vomiting 813. Most notably, Tack et al have found in multiple randomized placebo-controlled trials that mirtazapine is effective for nausea and other symptoms in functional dyspepsia, a condition with similar symptomatology to gastroparesis 5,7. However, there are only a handful of case reports on the effect of mirtazapine in gastroparesis.…”
Section: Introductionmentioning
confidence: 99%